2020
DOI: 10.1007/s11277-020-07700-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Binary Hexagonal Extrema Pattern (EBHXEP) Descriptor for Iris Liveness Detection

Abstract: Biometric traits are frequently used by security agencies for automatic recognition of a person. There are numerous biometric traits used for person identification. In recent years, iris biometric trait becomes very popular and efficient in many security applications. However, biometric systems are prone to presentation attack. This attack is carried out by using spoofing of any biometric modality and present as a genuine trait. The effect of an artificial artifact of a humanoid iris could be in the form of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The experiment was conducted for manually created sense inventories for about 60 polysemous nouns. The maximum precision achieved is 54.54% [19].…”
Section: Literature Surveymentioning
confidence: 92%
“…The experiment was conducted for manually created sense inventories for about 60 polysemous nouns. The maximum precision achieved is 54.54% [19].…”
Section: Literature Surveymentioning
confidence: 92%
“…Through careful manipulation of image, the solution can be deceived. Agarwal et al [18] proposed a local descriptor for detecting iris spoofing. The descriptor is productive and learns correlation for a pixel with its hexagonal neighbors.…”
Section: Related Workmentioning
confidence: 99%
“…Higher error due to surrounding artificial light sources Chou et al [15] Challenge response in terms of audio feedback Can be deceived easily Boutellaa et al [16] Voice modality based challenge response Can be deceived using voice faking Wang et al [17] Analyzed depth information from image captured using two cameras Can be deceived with careful manipulation of image Agarwal et al [18] local descriptor for detecting iris spoofing. Fails for video replay attacks Bhogal et al [19] six different picture quality measures to assess genuine biometric attributes easy to create masks to deceive these quality measures Fathy et al [20] Thresholded entropy esteems to detect iris spoofing Fails in case of illuminations Nguyen et al [21] Multi modal acquiring iris acquisition with varying light intensities.…”
Section: A Liveliness Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a subset of digital imaging. This versatile technique [2] can process both visual images and analog images. Agarwal et al demonstrated various prominent imaging techniques, and explained how they have been used in practice.…”
Section: Introductionmentioning
confidence: 99%